Pengembangan Media Jelajah Nusantara Untuk Siswa Sekolah Dasar - Febri Tri Hariyadi; M. Iqbal Baihaqi; Ida Putriani (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2023)
One of the obstacles to thematic learning in grade IV is the difficulty of the teacher in using the media. This study aims to develop the J Explore Nusantara media. The type of research used is Research and Development (R&D). The results of the feasibility of the media based on material experts showed very feasible results with a score of 82%, linguists stated that they were very feasible with a score of 90%, and media experts showed very feasible with a score of 87%. In the media readability test, it got a score of 95% and got a good response of 93% from students and 90% from teachers. So, it is concluded that the J Cruising Nusantara media is suitable for use in class IV.